2006
DOI: 10.1152/ajpcell.00482.2004
|View full text |Cite
|
Sign up to set email alerts
|

Activation of large-conductance, Ca2+-activated K+ channels by cannabinoids

Abstract: We have examined the effects of the cannabinoid anandamide (AEA) and its stable analog, methanandamide (methAEA), on large-conductance, Ca 2ϩ -activated K ϩ (BK) channels using human embryonic kidney (HEK)-293 cells, in which the ␣-subunit of the BK channel (BK-␣), both ␣-and ␤ 1-subunits (BK-␣␤1), or both ␣-and ␤4-subunits (BK-␣␤4) were heterologously expressed. In a whole cell voltage-clamp configuration, each cannabinoid activated BK-␣␤ 1 within a similar concentration range. Because methAEA could potentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 46 publications
3
27
0
Order By: Relevance
“…In agreement with our results, several earlier studies indicated that different types K ϩ channels are modulated by anandamide in a cannabinoid receptor-independent manner (Poling et al, 1996;Van den Bossche and Vanheel, 2000;Maingret et al, 2001;Oliver et al, 2004;Sade et al, 2006). Anandamide belongs to a class of signaling lipids consisting of amides of long-chain polyunsaturated fatty acids (Howlett et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with our results, several earlier studies indicated that different types K ϩ channels are modulated by anandamide in a cannabinoid receptor-independent manner (Poling et al, 1996;Van den Bossche and Vanheel, 2000;Maingret et al, 2001;Oliver et al, 2004;Sade et al, 2006). Anandamide belongs to a class of signaling lipids consisting of amides of long-chain polyunsaturated fatty acids (Howlett et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…For example, in excitable cells such as neurons, the activation of cannabinoid receptors by anandamide suppresses the presynaptic release of various neurotransmitters by inhibiting the function of voltage-dependent Ca 2ϩ channels (Howlett et al, 2002). Other studies have shown that anandamide modulates K ϩ channels (Poling et al, 1996;Van den Bossche and Vanheel, 2000;Maingret et al, 2001;Oliver et al, 2004;Sade et al, 2006). ATP-sensitive potassium (K ATP ) channels form an important link between metabolic state and cell excitability.…”
mentioning
confidence: 99%
“…Results obtained in experiments with rat isolated coronary arteries also suggest that such activation can be produced by both anandamide and R-(ϩ)-methanandamide at concentrations of 0.3 to 3 M, although not by JWH-133 at 1 M (Sade et al, 2006).…”
Section: Potassium Channelsmentioning
confidence: 84%
“…Thus, it has been found that this endocannabinoid induces such an increase in BK-αβ 1 channels expressed by HEK-293 cells, at 0.3, 1 and 3 μM (Sade et al 2006), in human BK K Ca channels expressed by HEK-293 cells, with an EC 50 value of 4.8 μM (Godlewski et al 2009), and in small conductance calcium-activated SK K Ca channels expressed naturally by rat cultured hippocampal neurons, at 1-100 nM (Wang et al 2011). Evidence was obtained as well in some of these investigations that anandamide did not increase K þ currents in BK or SK K Ca channels by acting on CB 1 or CB 2 receptors or indeed on TRPV1 channels (Sade et al 2006;Wang et al 2011). There has been a report too that outward K þ currents in BK K Ca channels expressed by HEK-293 cells are unaffected by 2-arachidonoylglycerol (10 μM) and that they are decreased by virodhamine with an IC 50 value of 447 nM (Godlewski et al 2009).…”
Section: Voltage-gated K V and K Ca Channels Of The 6tm Domain Familymentioning
confidence: 91%